2022
DOI: 10.3390/microorganisms10020305
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Carboxyhemoglobin Level Variation in COVID-19 and Bacterial Sepsis: A Novel Approach?

Abstract: Background: The increased production of carbon monoxide (CO) in sepsis has been proven, but the blood level variations of carboxyhemoglobin (COHb) as a potential evolutionary parameter of COVID-19 and sepsis/septic shock have yet to be determined. This study aims to evaluate the serum level variation of COHb as a potential evolutionary parameter in COVID-19 critically ill patients and in bacterial sepsis. Materials and method: A prospective and observational study was conducted on two groups of patients: the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
1
3
1
Order By: Relevance
“…Another study published in 2023 by G. Vadar and E. Ozek studied COHb levels in late-onset sepsis in pre-term neonates and found increased levels of COHb in the beginning of sepsis that decreased in response to antibiotics, but the variation of COHb, when used in conjunction with other sepsis biomarkers, could predict the outcome of sepsis [ 22 ]. Our study found an increase in COHb levels from D1 to D5 in both sepsis and septic shock non-survivors, comparable results to to recent literature [ 13 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Another study published in 2023 by G. Vadar and E. Ozek studied COHb levels in late-onset sepsis in pre-term neonates and found increased levels of COHb in the beginning of sepsis that decreased in response to antibiotics, but the variation of COHb, when used in conjunction with other sepsis biomarkers, could predict the outcome of sepsis [ 22 ]. Our study found an increase in COHb levels from D1 to D5 in both sepsis and septic shock non-survivors, comparable results to to recent literature [ 13 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Production of endogenous CO is the result of heme catabolism by heme oxygenase enzymes [ 12 ]. Disruption of heme metabolism and liver dysfunction associated with sepsis leads to an increase of COHb levels mainly due to oxidative stress, hypoxia, cytokines, endotoxins, and inflammatory mediators [ 13 , 20 ]. COHb is a parameter measured frequently in ICU during routine arterial blood gas analysis, an abrupt change of trend in COHb levels could lead the physician to notice a new course of the disease [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are conflicting results in critically ill adult patients regarding a correlation between serum lactate and COHb in the literature. 28,29 However, we found no correlation between serum lactate and COHb in the present study. In an experimental animal model, intestinal HO-1 expression increased in NEC.…”
Section: Statistical Analysis "Ibm Spss Statistics Forcontrasting
confidence: 87%
“…A total of 154 infants met the inclusion criteria of the study. The LOS group consisted of 77 newborns with an average gestation week and birth weight of 28 (26)(27)(28)(29)(30)(31)(32) weeks and 1030 (720-1745) gr, respectively. The onset time of LOS, calculated as the median, was 19 days in the study group.…”
Section: Statistical Analysis "Ibm Spss Statistics Formentioning
confidence: 99%